(untitled) (International Seven Journal of Multidisciplinary, 2025)
The objective is to investigate the importance of psychomotor skills in the development of children with Autism Spectrum Disorder (ASD), highlighting the role of physical therapy as a therapeutic method for promoting motor, cognitive, and social development. This is an integrative literature review, screening scientific articles published between 2018 and 2024 in the LILACS, SciELO, and Google Scholar databases. Studies in Portuguese, English, and Spanish that addressed the relationship between psychomotor skills, ASD, and physical therapy were included. The studies considered indicate that psychomotor skills, combined with physical therapy, significantly contribute to fine and gross motor development, balance, coordination, and body awareness, in addition to improving social interaction and reducing stereotypical behaviors. Psychomotor skills are an essential tool in the therapeutic process for children with ASD, promoting functionality, autonomy, and quality of life. The integrated work of physical therapists and other professionals in the multidisciplinary team encourages results, reinforcing the need for early and individualized interventions.